EFEKTIVITAS STRATEGI PEMBERIAN UMPAN BALIK TERHADAP KINERJA PRAKTIKUM MAHASISWA D-3 JURUSAN TEKNIK ELEKTRONIKA - Haryoko, Sapto (Jurnal Cakrawala Pendidikan, 2015)
Abstract: Effectiveness of the Feedback Providing Strategies on the Practicum Performance of the Students of the Diploma Three (D-3) of the Electronic Engineering Department. This study aims to investigate the effectiveness of the feedback providing strategies (immediate feedback and delayed feedback) on students' performance in the Electronics lab course. This study was an experiment employed a posttest-only control group design. The subjects were students of the Diploma Three (D-3) Program of the Electronic Engineering Department of FT UNM, divided into two treatment groups. Group A, consisting of 20 students, received the treatment of the immediate feedback and Group B, consisting of 19 students, received the treatment of delayed feedback. The data on the students' mastery of lab materials were collected through observations using a performance assessment form. The data were analyzed using the t-test. The results showed that the practicum performance of the students receiving immediate feedback was better than that of the students receiving delayed feedback. Keywords: immediate feedback, delayed feedback, students' practicum performance